Immunogenicity and Protective Efficacy of a Vero Cell Culture-Derived Whole-Virus H7N9 Vaccine in Mice and Guinea Pigs - Wodal, Walter (PLoS One, 2015)
BACKGROUND: A novel avian H7N9 virus with a high case fatality rate in humans emerged in China in 2013. We evaluated the immunogenicity and protective efficacy of a candidate Vero cell culture-derived whole-virus H7N9 vaccine in small animal models. METHODS: Antibody responses induced in immunized DBA/2J mice and guinea pigs were evaluated by hemagglutination inhibition (HI), microneutralization (MN), and neuraminidase inhibition (NAi) assays. T-helper cell responses and IgG subclass responses in mice were analyzed by ELISPOT and ELISA, respectively. Vaccine efficacy against lethal challenge with wild-type H7N9 virus was evaluated in immunized mice. H7N9-specific antibody responses induced in mice and guinea pigs were compared to those induced by a licensed whole-virus pandemic H1N1 (H1N1pdm09) vaccine. RESULTS: The whole-virus H7N9 vaccine induced dose-dependent H7N9-specific HI, MN and NAi antibodies in mice and guinea pigs. Evaluation of T-helper cell responses and IgG subclasses indicated the induction of a balanced Th1/Th2 response. Immunized mice were protected against lethal H7N9 challenge in a dose-dependent manner. H7N9 and H1N1pdm09 vaccines were similarly immunogenic. CONCLUSIONS: The induction of H7N9-specific antibody and T cell responses and protection against lethal challenge suggest that the Vero cell culture-derived whole-virus vaccine would provide an effective intervention against the H7N9 virus.